Bargaining and International Policy Cooperation - Rogoff, Kenneth (American Economic Review, 1990)
The past decade has witnessed the growth of a large literature on international cooperation in trade and macroeconomic stabilization policy. Virtually all the models developed to date, however, are based on one of two extreme assumptions concerning governments' ability to commit to international agreements. Either they assume that governments can make constitutionally binding long-term agreements, or else they assume that governments have no ability to make legal commitments whatsoever. In the latter case, international policy cooperation is possible only to the extent that reputational factors will allow.' In this paper, I consider a world in which there is no legal mechanism for enforcing long-term international agreements, but where governments must still incur some small direct costs if they renege. These small costs might arise due to legislative or administrative frictions. I also allow for the possibility that international economic policy agreements can include small sidepayments. For example, in negotiating a bilateral reduction in tariffs, two allies could simultaneously agree to redistribute the burdens of defense expenditures.